HUBUNGAN PERAN ORANG TUA, PERAN TEMAN, MEDIA SOSIAL TERHADAP IMPLEMENTASI PENDIDIKAN SEKS PADA ANAK DI KELURAHAN 16 ILIR PALEMBANG - Chodijah, Siti; Hasanah, Hafizotun; Putri Sari, Yemmy; Tedengki, Rein (Jurnal Medicare, 2025)
The implementation of sex education for children refers to the provision of information and guidance received by children aged 7–14 years related to sexual education, including understanding and maintaining reproductive hygiene, recognizing forms of sexual harassment, and being able to protect themselves from sexual abuse. This study aims to analyze the implementation of sex education for children in the 16 Ilir sub-district of Palembang. The population in this study includes all children aged 7–13 years residing in the 16 Ilir sub-district of Palembang. A total of 96 respondents were selected as the sample using the total sampling technique. Data were analyzed using univariate and bivariate methods with the chi-square test at an alpha level of 0.05. The results of the chi-square test indicate that there is a relationship between the implementation of sex education in children and the roles of parents, peers, and social media. Based on the findings, it is recommended that parents, in particular, take an active role in providing early sex education to their children using age-appropriate language.